Blockchain Based Cross Chain Trusted Clinical Records Sharing System - Goswami, Chandrshekhar; Reddy L., Sreenivasulu; Pankajam, A.; K., Priyadarsini; Solavande, Vivek Dadasaheb; Gopi, Adapa (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The progress of clinical informatization depends greatly on the trustworthy exchange of electronic healthcare records, which are sensitive and important private data assets for patients. The longer access time, problematic cross-domain trustworthy exchange, and insecure storage of patient clinical record data are all discussed in this study. Designing a cross-chain trustworthy sharing solution for electronic clinical records based on the Fabric alliance chain required the use of blockchain and edge computing in this work. The system is separated into patient mobile applications, hospital online applications, and RFID electronic tag wristbands, with clinical record encryption and authentication, cross-chain trustworthy sharing, remote authorization, and other features. Additionally, in order to accomplish tailored privacy protection, a system for controlling the flow of private data using patients as the main source is proposed in this work. This mechanism is based on a biometric key and a secret algorithm. In order to establish reliable access and control, the master-slave multi-chain layered cross-chain paradigm based on the upgraded PBFT consensus algorithm for the main Chain and PoVT consensus algorithm for the slave Chain is employed